The relationship between interpersonal intelligence and linguistic intelligence with mathematics learning achievement in high school students - Fransiskus Hardi; Maximus Tamur; Fransiskus Nendi (Journal of Didactic Mathematics, 2021)
In teaching, the teacher emphasizes identifying the dominant intelligence and learning styles to improve student achievement. However, exploring interpersonal and linguistic intelligence and its relationship to student achievement is still rarely done. This correlational research was conducted to describe the relationship between interpersonal and linguistic intelligence with high school students' mathematics learning achievement. The samples of this study were students of class XI SMA Budi Dharma Cancar Indonesia (n=30). The data were collected using a questionnaire and the pure grades of the students' midterm exams. The data analysis technique uses Product Moment Correlation as a statistical test tool to test the hypothesis of the relationship between two variables after fulfilling the prerequisite test. The results showed a positive relationship between interpersonal and linguistic intelligence and students' mathematics learning achievement. Although this study was limited to two bits of intelligence, it is essential to note that the findings of this study indicate that the number of intelligence at the dominant level can predict learning achievement in school.